Profil Pemahaman Konsep Evolusi Mahasiswa Calon Guru Biologi FPMIPA IKIP Mataram - Firdaus, Laras; Samsuri, Taufik; Hunaepi, Hunaepi; Mirawati, Baiq (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2019)
[Title: The Conceptual Profile of Prospective Biology Teacher FPMIPA IKIP Mataram]. The conceptual profile is a tool for analyzing the style or process of thinking, so the profile of understanding concepts is very important to study as a basis for designing and improving the quality of learning. This research is a descriptive study that aims to identify and explain the conceptual profile of prospective biology teacher FPMIPA IKIP Mataram. The subjects in this study included all biology students who regularly program evolutionary courses. The open-ended question is designed to collect conceptual profile data on the evolutionary biology students from FPMIPA IKIP Mataram. Identification or determination of conceptual profile is based on student responses or answers. Based on the results of the research and the limitations of the discussion, it is recommended that the development of textbooks that are free of misconception as a learning resource for valid biology prospective teacher, then lecturers as instructors, continue to study and teach about attitude, namely scientific attitudes, or thinking dispositions, and/or integrating attitudes in the lecture process. Besides that, in the lecture or learning process, the lecturer must facilitate or empower the style or process of thinking of students with various learning methods or strategies that emphasize thinking processes, including formal reasoning, and analogical teaching strategy.